The impact of COVID-19 lockdown restrictions on missing person reports - O’Brien, Freya (Policing and society, 2022)
The COVID-19 pandemic and the resultant restrictions imposed by governments pose short- and long-term challenges for the police, especially within resource-intensive areas of policing such as missing persons. However, the novelty of the pandemic means little research focus has been directed at understanding these challenges and how they may be overcome. Using archival reports from six UK police forces, the current study examined the extent to which missing persons cases changed during the first UK COVID-19 lockdown. Using a non-experimental fixed design, differences in the characteristics of reports of both children and adults who went missing between March and May 2020 and the same time period in 2019 were examined. Findings suggest a substantial reduction in missing reports overall, but a shift in the proportions of types of cases reported. For example, there was a greater proportion of adults classified as high risk of harm during this period and a greater proportion of children who were deemed low risk, who were living in residential care, and who were not from a White British background. Although forces must consider the findings within their local context, the study has implications in terms of demand and allocation of police resources, as well as multi-agency working. Future research is discussed.